Control Delivery of Multiple Growth Factors to Actively Steer Differentiation and Extracellular Matrix Protein Production. Issue 4 (22nd March 2021) - Damanik, Febriyani F. R.; Verkoelen, Niels; van Blitterswijk, Clemens; Rotmans, Joris; Moroni, Lorenzo
Abstract: In tissue engineering, biomaterials have been used to steer the host response. This determines the outcome of tissue regeneration, which is modulated by multiple growth factors (GFs). Hence, a sustainable delivery system for GFs is necessary to control tissue regeneration actively. A delivery technique of single and multiple GF combinations, using a layer‐by‐layer (LBL) procedure to improve tissue remodeling, is developed. TGF‐β1, PDGF‐ ββ, and IGF‐1 are incorporated on tailor‐made polymeric rods, which could be used as a tool for potential tissue engineering applications, such as templates to induce the formation of in situ tissue engineered blood vessels (TEBVs). Cell response is analyzed in vitro using rat and human dermal fibroblasts for cellular proliferation, fibroblast differentiation, and extracellular matrix (ECM) protein synthesis. Results revealed a higher loading efficiency and control release of GFs incorporated on chloroform and oxygen plasma‐activated (COX) rods. Single PDGF‐ ββ and IGF‐1 release, and dual release with TGF‐β1 from COX rods, showed higher cell proliferation when compared to COX rods alone. A substantial increase in α‐smooth muscle actin (α‐SMA) is also observed in GF releasing COX rods, with TGF‐β1 COX rods providing the most pronounced differentiation. A significant increase in collagen and elastin synthesis is observed on all GF releasing COX rods compared to control, with COX rods releasing TGF‐β1 and IGF‐1 providing the highest secretion. TGF‐β1 and IGF‐1 releasing COX rods induced higher Glycosaminoglycan (GAG)/DNA amounts than the other GF releasing COX rods. As PDGF‐ ββ and TGF‐β1/PDGF‐ ββ COX rods displayed the highest fibroblast attachment, these rods provided the highest total collagen and elastin production. The attractive results from efficiently incorporating single and multiple GFs on COX rods and their sustainable release to steer cellular behavior suggest a promising route to enrich the formation of in situ engineered tissues. Abstract : Layer‐by‐layer coating of a biomaterial device allows the controlled delivery of dual growth factors. The resulting devices elicit fibroblasts transdifferentiation into myofibroblasts and enhanced extracellular matrix protein secretion, which may be used for in situ tissue regeneration applications.